EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN MEDIA WHATSAPP UNTUK MEREDUKSI ANXIETY TERHADAP BAHAYA COVID-19 - Fadliansyah, Ahmad; Humaera, Siti (Universitas Sahid Surakarta, 2021)
This study aims to determine whether providing information services using WhatsApp media is effective in reducing anxiety against the dangers of COVID-19. This research is using experimental method. The research design used was a one group pre-testposttest pre-experimental design. Based on the results of data analysis, using the t-test value, the t-count value is obtained = 7.280, then the t-count value is consulted with the t-table at db = N-1 (13-1) = 12, at a significant level of 5% and 1% obtained 2.179 and 1.782 (2.179 <7,280> 1,782). Thus the research hypothesis that